Pengaruh Leverage, Struktur Kepemilikan, dan Inovasi Terhadap Kinerja Keuangan pada Perusahaan Sektor Infrastruktur, Utilitas, dan Transportasi Periode 2019-2023 - Sari, Septiana Dewi Kartika; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2025)
This study aims to examine the effects of leverage, ownership structure, and innovation on the financial performance of firms. A quantitative approach was employed, utilising secondary data sourced from companies in the infrastructure, utility, and transportation sectors listed on the Indonesia Stock Exchange during the period 2019–2023. The sample consisted of 30 companies selected through purposive sampling. Data analysis was conducted using multiple linear regression with IBM SPSS 25. The findings indicate that leverage has a significant negative effect on financial performance, as measured by return on assets (ROA). This suggests that excessive reliance on debt may lead to financial distress due to increased interest obligations, although debt utilisation can be beneficial when tax shields outweigh the costs. Furthermore, managerial and institutional ownership, components of ownership structure, exert a significant positive influence on financial performance, likely due to their role in mitigating agency conflicts between principals and agents. However, ownership concentration was found to have no significant impact on performance. Innovation also demonstrated a significant positive effect on financial performance. Based on these results, firms are advised to manage leverage carefully, as higher debt levels can adversely affect performance. Conversely, enhancing managerial and institutional ownership, alongside fostering innovation, may serve as effective strategies for improving financial outcomes.